Analisis Kerusakan Spherical Bearing Pada Roller Grinding Atox Mill K1m01 Di Area Coal Mill PT. Semen Baturaja I (Persero) Tbk Indonesia - Agus, Muhammad Jepri; Syafri, Syafri; Cupu, Dedi Rosa Putra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Roller Grinding at Atox Coal Mill is equipment used to refine coal (raw coal). In the atox mill have three roller grinding. The movement of the roller grinding comes from the table's movement under the grinding roller. The lubrication system on the roller grinding is rated on the outside lubrication system.Roller grinding in atox vertical mill is a device that used a large bearing type of heavy duty. The method on spherical damage analysis used the data that exists in the field and data theoretically calculations so the purpose of this calculation is to find out the age bearing with the type of damage occurring on bearing, and to know the age of bearing SKF 23068 CAC on roller three grinding atox mill with a bearing speed on the bearing age, that the speed of bearing screening affects the thickness of a film layer. The faster of sphere, the thinner layer film is resulting.. Keywords: Roller grinding, caol mill, bearings